Effect Of Blended Learning On Independence And Learning Outcomes Of Grade Xi Learners - Khatimah, Khusnul; Adnan, Adnan; Pagarra, Halifah (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
Research was carried out with the aim of finding out blended learning on the independence and learning outcomes of class XI MAN 1 Makassar City students. A posttest only control design was used in this research, which is a type of quasiexperimental research. Entire class of XI MAN 1 Makassar City, consisting of 12 classes, was used as the population, then selected by random sampling to obtain 4 classes as samples consisting of 3 experimental classes and 1 control class. Implementation of learning in experimental group used an ICT-based MPBK model with blended learning approach, while in the control group used direct instruction learning model with teacher-based learning approach. Data collection on learning independence is non-test instrument in the form of questionnaire and data collection on learning outcomes is test instrument in form of objective and subjective questions. Data results were then analyzed using descriptive statistics followed inferential statistics. Results of the descriptive analysis showed that the experimental group had better independence and learning outcomes than tcontrol group. Results of the inferential analysis used normality tests, homogeneity, hypothesis testing with multivariate analysis of variance tests and further Tukey HSD tests. From hypothesis testing it was found that the significance value was 0.000 < 0.05, so there was influence of blended learning on independence and learning outcomes of class XI MAN 1 Makassar City students. Results of further tests with Tukey HSD for independence and learning outcomes showed that experimental and control groups were in different subset columns so that there were significant differences between groups, which means that statistically blended learning has influence on students' independence and learning outcomes.